Respon Kiai Pesantren terhadap Materi Kompilasi Hukum Islam di Indonesia (Studi Kasus di Kota Jambi) - Ibad, Saiful; Rasito, Rasito (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
This study aims at explaining how kiais of pesantrens in Jambi City respond to the Compilation of Islamic Law in Indonesia. It uses anthropological approach with descriptive analysis. The data was collected with limited participatory, observation, and interview. The results of this study shows that the acceptance and objection of the kiais to the Compilation of Islamic Law in Indonesia have been very much infiuenced by Islamic literatures, organizations and their lines of teachers. It is, therefore, the government should reconsider the existence of Inpres (Instruksi Presiden, or the Presidents Instruction) number l, 1991, because the Inpres was not well responded by kiais who teach Islamic teachings and give fatwa (religious advice) to Muslim communty.